DEVELOPING LESSON PLAN OF TEACHING THE USE OF FIGURATIVE LANGUAGE IN THEIR CONTEXT - Luthfihayati, Dian (E-Link Journal, 2016)
Semantic  is one of the branches of linguistics studying about meaning. Meanings are ideas or concepts that can be transferred from the mind of the speaker to the mind of the hearer. As we know that sometimes similar expression may have different meaningif  it is used in different contextKeywords: lesson plan, teaching, figurative language